ANALISIS MUTU BISKUIT TEPUNG IKAN PATIN (PANGASIUS SP.) DAN TEPUNG KACANG MERAH (PHASEOLUS VULGARIS) SEBAGAI MP-ASI INSTAN TINGGI PROTEIN UNTUK ANAK (1-2 TAHUN) - Sanjaya, Dandi; Hastuti, Widi; Fitria, Mona; Rahmat, Mamat; Isdiany, Nitta; Pusparini, Pusparini (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Riskesdas 2018 shows 4.5% of 1-2 year old children experience poor nutritional status. The reason is the low quality of MP-ASI and inappropriate parenting. Local foods such as catfish and red beans can be made MP-ASI. Catfish is a freshwater fish with high protein (12-17.5%) and low fat (0.9-1.2%) with a production of 437,111 tons. Red beans are a source of vegetable protein (22%) with a production of 67,876 tons. The catfish and red beans were made into flour, then formulated as MP-ASI biscuits. This study aims to determine the organoleptic properties (color, aroma, taste, texture, and overall) and nutritional content (energy, protein, fat, carbohydrates and iron) of MP-ASI biscuits. The design of this research is an experimental study. Product quality analysis includes organoleptic properties, macronutrients, and iron. Organoleptic test using hedonic test on 3 biscuit formulations with a ratio of catfish flour and red bean flour, namely F1 (35%: 65%), F2 (40%: 60%) and F3 (45%: 65%). The results of the organoleptic test by 30 panelists showed that the best formula was F1 with an average score of color (5.7), aroma (5.3), taste (5.1), texture (5.4), and overall (5.5). ). Each serving of MP-ASI biscuits (50 g) contains 173.2 kcal of energy, 30.4 g of carbohydrates, 4.7 g of protein, 3.5 g of fat and 0.07 mg of iron (Fe). The selling price per serving weighing 50 g (5 pieces) is Rp. 4.237. This MP-ASI biscuit can be used as a snack for children (1-2 years), but it has a slightly fishy and slightly unpleasant aroma and a slightly hard texture, so it is hoped that it can be improved in future research.